THE RELATIONSHIP OF KNOWLEDGE LEVEL ABOUT CLEAN AND HEALTHY LIVING BEHAVIOR WITH THE INCIDENCE OF DIARRHEA IN CHILDREN AT LENTENG TIMUR 1 PUBLIC ELEMENTARY SCHOOL DISTRICT LENTENG SUMENEP MADURA - Choles, Shilviana Nur; Sasmito, Nanang Bagus; Zatihulwani, Eliza Zihni; Puspita, Enny (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2023)
Background: Diarrhea disease is included in the Extraordinary Events category in various parts of Indonesia that needs attention. Globally, data on the incidence of diarrhea in the world are still very high, namely 1.7 billion cases every year or the second cause of death that attacks children (WHO, 2017). The study revealed that approximately 8 out of every 10 sixth-grade students at Lenteng Timur 1 Public Elementary School had encountered instances of diarrhea. Objective: The aim of this research was to establish a correlation between the degree of understanding regarding knowledge about clean and halthy living behavior and the occurrence of diarrhea among children. Method: The chosen research methodology is analytical correlation employing a cross-sectional approach design. This research was carried out in Lenteng Timur 1 Public Elementary School, Lenteng District, Sumenep Regency, Madura on Wednesday 24 May 2023. This investigation selected a sample of 42 students, gathering data through a comprehensive sampling technique. The research instrument used in this study was Medi Arjoni's (2021) knowledge level questionnaire. The statistical analysis employed for this study was SPSS version 20 for Windows 11. Results: The results showed that the level of knowledge about clean and healthy living behavior was less than 18 students (42.9%), the incidence of diarrhea during the last 3 months was 25 students (59.5%). Analysis of the extent of understanding in relation to the occurrence of diarrhea p- value<α, namely 0.001<0.05. The conclusion of this study is that there is a relationship between the lack of knowledge about clean and healthy living behavior and the incidence of diarrhea in class VI children of Lenteng Timur 1 Public Elementary School. Conclusion: The suggestion from the researchers aims to enhance comprehension regarding clean and healthy living behavior to support the productivity of a healthy body and a clean environment in everyday life so that they are not easily exposed to disease and reduce the incidence of diarrhea in children.